An annotated checklist of the New World pentodontine scarab beetles (Coleoptera: Scarabaeidae: Dynastinae: Pentodontini) - López-García, Margarita M.; Gasca-Álvarez, Héctor J.; Cave, Ronald D.; Amat-García, Germán (Zootaxa, 2016)
An updated and annotated checklist of the Pentodontini (Coleoptera: Scarabaeidae: Dynastinae) of the New World is presented. The tribe is composed of 32 genera and 151 species, including the introduced species Heteronychus arator (Fabricius).